1992
DOI: 10.1121/1.402494
|View full text |Cite
|
Sign up to set email alerts
|

Transient response of thick circular and square bars subjected to transverse elastic impact

Abstract: The objective of the studies presented in this paper was to understand the transient response of thick circular and square bars subjected to transverse elastic point impact. It is shown that the transient response is composed of a number of resonant frequencies caused by cross-sectional modes of vibration. The individual cross-sectional modes and their corresponding natural frequencies were determined using plane strain and three-dimensional finite-element models of circular and square cross sections. The firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 0 publications
1
13
0
1
Order By: Relevance
“…Experimental studies have been supplemented with analytical studies to gain a better understanding of the propagation of transient waves in bounded solids with and without flaws [Cheng and Sansalone 1993a, 1993b, 1995a, 1995bLin et al, 1991aLin et al, , 1991bSansalone et al, 1987aSansalone et al, , 1987b. Application of the method has been extended to prismatic members, such as columns and beams [Lin and Sansalone, 1992a, 1992b, 1992c. It has been found that reflections from the perimeter of these members cause complex modes of vibration.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies have been supplemented with analytical studies to gain a better understanding of the propagation of transient waves in bounded solids with and without flaws [Cheng and Sansalone 1993a, 1993b, 1995a, 1995bLin et al, 1991aLin et al, , 1991bSansalone et al, 1987aSansalone et al, , 1987b. Application of the method has been extended to prismatic members, such as columns and beams [Lin and Sansalone, 1992a, 1992b, 1992c. It has been found that reflections from the perimeter of these members cause complex modes of vibration.…”
Section: Applicationsmentioning
confidence: 99%
“…It has been found that reflections from the perimeter of these members cause complex modes of vibration. Figure 11 shows an example of the shapes associated with the modes of vibration of a square beam or column [Lin and Sansalone, 1992b]. These modes result in an amplitude spectrum with many peaks, and the depth of the member is not related to the dominant frequency in the spectrum according to Eq.…”
Section: Applicationsmentioning
confidence: 99%
“…The size of the element should be smaller than one tenth the shortest propagating wavelength (Lin and Sansalone, 1992). A study of the convergence rate shows that 100 elements are sufficient to obtain high accuracy for the fundamental modes (Aalami, 1973).…”
Section: Finite Element Formulationmentioning
confidence: 99%
“…Поэтому параметры электрического отклика связаны с характе-100 Т.В. Фурса тов [10,22]. Многократное рассеяние акустических волн на неоднородностях и дефектах приводит к затуханию энергии акустического возбуждения, а следовательно, и электрического отклика.…”
Section: Introductionunclassified